Analysis of Public Satisfaction with Electronic Outpatient Registration Services at Ratu Zalecha Martapura Regional Hospital - Isti Qomah; Ni Wayan Kurnia Widya Wati; Faizah Wardhina (Journal of Health Management, Administration and Public Health Policies, 2025)
A hospital is an integral part of the social and medical organization, functioning to provide health services to the community, both curative and rehabilitative. Every health service facility has an obligation to be accountable for the services provided. One form of accountability is the provision of health information through the implementation of technology in hospitals, specifically the use of electronic medical records (EMR) to manage patient medical documentation, with the aim of improving service quality and achieving user satisfaction. User satisfaction in utilizing EMR serves as one of the indicators of successful implementation of the information system. This study aims to analyze community satisfaction with electronic outpatient registration services at RSUD Ratu Zalecha Martapura in 2024. The research employed an analytical survey method. The population consisted of all patients who registered for outpatient services through the SIPO RAZA and Mobile JKN applications at RSUD Ratu Zalecha Martapura, with a total of 47 respondents selected using accidental sampling.The results of the study, analyzed using the Spearman rho test, yielded a p-value of 0.062 > α = 0.05, indicating that there is no significant relationship between community satisfaction and the electronic outpatient registration services at RSUD Ratu Zalecha Martapura.